Pengaruh Video Animasi terhadap Kemampuan Bercerita Anak Usia 5-6 Tahun - Wahyuni, Jasri; Yulsyofriend; Yaswinda; Zulminiati (Universitas Lancang Kuning, 2025)
This research is motivated by problems based on empirical data that reveal that children's storytelling ability in terms of language has not developed. For example, children's language skills have not developed, especially in storytelling activities, they lack mastery of understanding, are not yet able to construct simple sentences, and are not yet able to understand the contents of the story being conveyed. In addition, learning still uses media that are less interesting to stimulate children's language skills. This study utilizes a quantitative approach with a quasi-experimental method. Bhakti Bunda Kindergarten is the location of this research. All children at Bhakti Bunda Kindergarten Padang are the research population. The sampling technique utilized was (purposive sampling), with 10 children in each group B2 and B3 who became the control and experimental classes, as research samples. The researcher used an oral test as a data collection method. Some techniques for data analysis are normality, homogeneity, and hypothesis tests. Considering data analysis, the average pre-test score of the experimental group was 16.2, while the average post-test score was 18.2. The control class had an average pre-test score of 14.7 and a post-test score of 15.6. The resulting data set had a normal and homogeneous distribution. The outcomes of the hypothesis testing indicated that animated videos had an influence on children's storytelling ability at Bhakti Bunda Padang Kindergarten, with a sig value (2-tailed) of 0.005 <0.05.